DNA Variations in Oculocutaneous Albinism: An Updated Mutation List and Current Outstanding Issues in Molecular Diagnostics. Issue 6 (30th April 2013) - Simeonov, Dimitre R.; Wang, Xinjing; Wang, Chen; Sergeev, Yuri; Dolinska, Monika; Bower, Matthew; Fischer, Roxanne; Winer, David; Dubrovsky, Genia; Balog, Joan Z.; Huizing, Marjan; Hart, Rachel; et al.
<x xml:space="preserve">Abstract</x> Isolated oculocutaneous albinism (OCA) is an autosomal recessive condition causing low vision and hypopigmentation. The article provides a mutation update for the OCA genes and discusses several challenging aspects of OCA molecular diagnostics, including the temperature sensitive TYR p.R402Q mutation, OCA‐1 subtyping and the presence of a substantial minority of affected individuals with apparent missing heritability. A comprehensive list of previously reported mutations is provided as supplementary material, and includes collated ethnicity information, carrier frequencies, and in silico pathogenicity predictions. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>